2010
DOI: 10.1038/jes.2010.6
|View full text |Cite
|
Sign up to set email alerts
|

Parabens in urine, serum and seminal plasma from healthy Danish men determined by liquid chromatography–tandem mass spectrometry (LC–MS/MS)

Abstract: Parabens are used as anti-microbial preservatives in a range of consumer products, especially in cosmetics. In vitro and animal studies have shown weak estrogenic and other endocrine disrupting effects of parabens, including reduced testosterone levels in exposed male rats. The knowledge of paraben exposure, distribution and excretion in humans is limited. In this study we determined the concentration of five parabens; methyl-, ethyl-, n-propyl-, n-butyl-and benzylparaben in urine, serum and seminal plasma sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
113
2
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 228 publications
(133 citation statements)
references
References 25 publications
13
113
2
5
Order By: Relevance
“…French and Spanish pregnant women and American women had higher paraben concentrations than the Danish women in our study (Calafat et al 2006, Casas et al 2011. In another recent Danish study, young men had slightly lower paraben levels than the pregnant women in this study (Frederiksen et al 2011). Americans have a slightly different phthalate excretion pattern than Danish and German women, with a higher excretion of MEP and lower MBP (Table 6).…”
Section: Discussioncontrasting
confidence: 32%
See 1 more Smart Citation
“…French and Spanish pregnant women and American women had higher paraben concentrations than the Danish women in our study (Calafat et al 2006, Casas et al 2011. In another recent Danish study, young men had slightly lower paraben levels than the pregnant women in this study (Frederiksen et al 2011). Americans have a slightly different phthalate excretion pattern than Danish and German women, with a higher excretion of MEP and lower MBP (Table 6).…”
Section: Discussioncontrasting
confidence: 32%
“…The total content (free and conjugated) of methylparaben (MeP), ethylparaben (EtP), n-propylparaben (n-PrP), isopropylparaben (i-PrP), n-butylparaben (n-BuP), iso-butylparaben (i-BuP) and benzylparaben (BzP) was simultaneously analysed by LC-MS/MS as previously described by Frederiksen et al (2011) with the following modification in order to separate i-PrP and n-PrP, and i-BuP and n-BuP, respectively, the solvent gradient described in Frederiksen et al (2010) for a LC-MS/MS method for phthalate metabolites was used. The retention time periods for the analytes were 6.2 min (MeP), 8.6 min (EtP), 12.0 min (i-PrP), 12.6 min (n-PrP), 17.0 min (i-BuP), 17.4 min (n-BuP) and 18.7 min (BzP).…”
Section: Parabensmentioning
confidence: 99%
“…The 2005-2006 National Health and Nutrition Examination Survey (NHANES) report indicated the presence of MeP and PrP in >90% of urine samples collected from the U.S. (Calafat et al, 2010). The presence of parabens in urine samples from Spain and Denmark also was documented Frederiksen et al, 2011). Studies have reported the occurrence of parabens in human plasma, serum, and milk at concentrations on the order of a few nanograms per milliliter (Frederiksen et al, 2011;Schlumpf et al, 2010;Wang et al, 2013;Ye et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A few biomonitoring studies have reported the occurrence of parabens in human urine, plasma, serum, and milk (Calafat et al, 2010;Casas et al, 2011;Darbre and Harvey, 2008;Frederiksen et al, 2011;Janjua et al, 2007;Schlumpf et al, 2010;Ye et al, 2006aYe et al, , 2006bYe et al, , 2008. MeP and PrP were found in >96% of urine samples collected from the U.S. (Ye et al, 2006a).…”
Section: Introductionmentioning
confidence: 99%
“…2 Although parabens are still considered safe, the potential endocrine disrupting effects of the exposure to high levels of these compounds have raised health concerns. 3 High concentrations of parabens in the breast tissue might be associated with breast cancer. Parabens can mimic estrogen action stimulating the growth of MCF7 cells, which are related to the development of breast cancer.…”
Section: Introductionmentioning
confidence: 99%